Antecedents And the Consequences of Supplier Adaptation to Restaurant Performance in Bogor City, Indonesia - Yuono, Karisa Intan Devanti; Santosa, Wahyuningsih (Golden Ratio of Data in Summary, 2025)
In increasingly fierce business competition, the role of supplier connections and design quality is becoming increasingly important. The research aims to analyze the influence of supplier connections and design quality on restaurant performance in the city of Bogor. The data source is primary data, namely a survey of business owners/managers and employees in the Bogor restaurant industry. Data collection was carried out by filling out a questionnaire. The analysis method uses Structural Equation Modeling, validity, reliability and goodness of fit tests. The results show that all question items are valid with factor loading greater than 0.5. The results of the reliability test show that all variables have a Cronbach Alpha above 0.7 (reliable). The goodness of fit test results shows model suitability (RMR). Coordination between suppliers and component design adjustments is relatively good. The quality of the supplier's adaptation to the restaurant's requirements indicates the supplier is prepared to address the requirements with specialist tools and equipment. The performance of the restaurant supply chain after having a supplier connection shows that the supplier has a good ability to reduce manufacturing operational costs.